Chaotic assessment of the heave and pitch dynamics motions of air cushion vehicles - Sowayan, Ahmed S. (Zielona Góra: Uniwersytet Zielonogórski)
In this study, a three degrees of freedom nonlinear air cushion vehicle (ACV) model is introduced to examine the dynamic behavior of the heave and pitch responses in addition to the cushion pressure of the ACV in both time and frequency domains. The model is based on the compressible flow Bernoulli's equation and the thermodynamics nonlinear isentropic relations along with the Newton second law of translation and rotation.
Keywords: air cushion vehicles; Poincaré map; Fast Fourier Transform (FFT); heave motion; pitching motion